Market development for multi-story wood construction : views of architects and structural engineers - Färnström, Isac (SLU/Dept. of Forest Economics, 2022)
The multi-story wood construction industry has been on the rise in the past decades because of new regulations making it legal in Sweden and Finland. Politicians have been suggesting more wood materials in buildings because of the positive environmental impact when wood stores carbon dioxide. Concrete is still the most used material in buildings and many developers have a poor perception of wood. The aim of this project was to analyze the wood construction industry in Sweden and Finland. More specifically to identify enabling and limiting factors and suggest measures for increased usage of wood. The method used was a qualitative and quantitative web survey directed to architects and structural engineers experienced in wood construction. The target group was reached by using connections from the project “Knock on wood” and reaching out to interest organizations. This project found that knowledge gaps among developers and contractors, high costs, and lack of standardized processes were limiting the industry. To overcome these issues and increase the usage of wood, the conclusion was: Industry actors need more education about wood construction, carbon taxes should be implemented on materials, and more prefabricated wood products should be made by the manufacturers.